Geneza i ujęcie przestępstw z powodów dyskryminacyjnych w polskim prawie karnym - Andrzej Pasek (Prawo)
The article presents the origins and framing of crimes on discriminatory grounds in Polish criminal law. It points out that the Criminal Code of 1932 criminalized discrimination solely on the grounds of protecting religious sentiment. This narrow formulation was expanded in special criminal laws issued after World War II. The author then analyzes the crimes for discriminatory reasons contained in the Small Criminal Code of June 13, 1946 and the Decree of August 5, 1949 on the Protection of Freedom of Conscience and Religion. The author emphasizes that these provisions set a further course in the treatment of discriminatory behavior under Polish criminal law and perpetuated its criminalization. He notes the signifi cant impact of the facts of crimes on discriminatory grounds contained in the two decrees on Article 193 and Article 274 of the 1969 Criminal Code. He further analyzes Article 257 of the 1997 Criminal Code in terms of countering manifestations of discrimination aimed at human dignity and integrity.